2021
DOI: 10.1111/imig.12942
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of refugees: Some reflections on definitions and measurement practices

Abstract: The notion of vulnerability originates in the environmental sciences, where it is viewed as "a powerful analytical tool for describing states of susceptibility to harm, powerlessness, and marginality of both physical and social systems" (Adger, 2006, p. 268). However, the diffusion of this notion well beyond the original field of application led Brown et al. (2017, p. 497) to point out how "the ubiquity and elasticity of [the term] vulnerability generates a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…As a theoretical lens through which to examine our findings, we drew on the syndemic theory, referring to the co-occurrence and interaction of social conditions and inequities, combined with the notion of intersectionality. Intersectional vulnerabilities, risks, and disadvantages based on characteristics such as gender, age and SES status – in the case of AGYW in our study – are produced and continually reproduced in a dynamic relationship, with a cumulative effect that exceeds the sum of the detrimental effects derived from each single characteristic [ 47 ]. Applying an intersectional lens to the concept of syndemics, which often focuses on individual vulnerabilities, adds a consideration the intersections at which an individual exists – gender, age, SES status – helping to account for a diversity of experiences within a population, explaining the resilience demonstrated by some AGYW in our sample [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a theoretical lens through which to examine our findings, we drew on the syndemic theory, referring to the co-occurrence and interaction of social conditions and inequities, combined with the notion of intersectionality. Intersectional vulnerabilities, risks, and disadvantages based on characteristics such as gender, age and SES status – in the case of AGYW in our study – are produced and continually reproduced in a dynamic relationship, with a cumulative effect that exceeds the sum of the detrimental effects derived from each single characteristic [ 47 ]. Applying an intersectional lens to the concept of syndemics, which often focuses on individual vulnerabilities, adds a consideration the intersections at which an individual exists – gender, age, SES status – helping to account for a diversity of experiences within a population, explaining the resilience demonstrated by some AGYW in our sample [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Applying an intersectional lens to the concept of syndemics, which often focuses on individual vulnerabilities, adds a consideration the intersections at which an individual exists – gender, age, SES status – helping to account for a diversity of experiences within a population, explaining the resilience demonstrated by some AGYW in our sample [ 48 ]. In this way, intersectionality and the syndemic theory can help to explain the ways in which intersectional vulnerabilities and risks combine to influence the ways different AGYW experience vulnerability and resilience [ 47 , 49 ]. Our data and that of other studies, suggest that SES status was an important determinant for how COVID-19 lockdowns were experienced, with poverty as a vulnerability factor that exacerbated pre-existing inequalities, negatively impacting on the wellbeing of poorer households.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultural barriers might particularly have an impact on medical compliance. Previous studies demonstrated that the lack of a common language between staff and patients is associated with decreased symptom reporting and fewer referrals to secondary and specialist care [ 41 ]. The lack of language skills to navigate the healthcare systems seems to be the prevalent barrier mentioned by researchers [ 61 , 62 , 63 , 92 , 93 , 94 , 95 , 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are considered vulnerable groups due to their challenging experiences before and during the displacement and the arrival in the host country. However, since vulnerability is a multi-layered concept, refugees should not be considered vulnerable per se; each person might be assessed on situational fragilities and needs [ 41 ]. Therefore, barriers and challenges to accessing healthcare need to be pointed out.…”
Section: Access To Healthcare For Asylum Seekers and Refugees: Focus ...mentioning
confidence: 99%